2016
DOI: 10.24141/2/2/3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in blind and partially sighted people

Abstract: The aim of this research was to examine the subjective quality of life in blind and partially sighted people in relation to the type of impairment, duration of impairment and participation in psychosocial rehabilitation. The study used a sociodemographic and health questionnaire, and the Personal Wellbeing Index for adults to examine participant satisfaction with different life domains. The results have shown that subjective quality of life in blind and partially sighted people is within the theoretically expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
3
8
0
1
Order By: Relevance
“…Moreover, it is noteworthy that all mean scores of PWB scale and QoL questionnaire were lower in severely sight-impaired subjects than in either blind or mildly sight-impaired subjects. These data may be consistent with the notion that the main difference between the blind and the severely sight-impaired subjects is that the former see their blindness as their characteristic trait, while the latter try to function as if they have normal sight [19]. Therefore, it can be hypothesized that the slight visual residue of severely sight-impaired subjects might represent a self barrier to the improvement of social skills and socialization level with consequent negative impact on PWB and QoL.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, it is noteworthy that all mean scores of PWB scale and QoL questionnaire were lower in severely sight-impaired subjects than in either blind or mildly sight-impaired subjects. These data may be consistent with the notion that the main difference between the blind and the severely sight-impaired subjects is that the former see their blindness as their characteristic trait, while the latter try to function as if they have normal sight [19]. Therefore, it can be hypothesized that the slight visual residue of severely sight-impaired subjects might represent a self barrier to the improvement of social skills and socialization level with consequent negative impact on PWB and QoL.…”
Section: Discussionsupporting
confidence: 84%
“…As far as differences related to the levels of visual disability are concerned, in line with literature data [19], mildly sight-impaired individuals reported better QoL than either blind or severely sight-impaired individuals mainly in the SF-12 mental score. Moreover, it is noteworthy that all mean scores of PWB scale and QoL questionnaire were lower in severely sight-impaired subjects than in either blind or mildly sight-impaired subjects.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In a study examining the impact of visual acuity (VA) on the ability to perform activities of daily living (ADL), even patients with mild vision impairment (20/40-20/70) were more likely to be limited in performing ADLs, and those with a moderate-to-severe visual impairment (>20/70) had an even greater likelihood of being limited (Daien et al 2014). Moreover, a recent study measuring quality of life (QOL) among both blind and low-vision individuals demonstrated that blind people had lower overall QOL scores than people with low vision as well as lower scores across nearly every QOL subscale, including health, relationships, community connectedness and achievements in life (Vuletic et al 2016). In addition, a large study of over 5000 blind individuals discovered that, compared with an age-and sex-matched e1212 control population, the blind population was more likely to have mental health conditions such as anxiety, depression and alcohol misuse (Court et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by numerous studies, people with limited mobility are exposed to social exclusion, which, we assume, is reflected in the results of this survey. According to data obtained independently by different researchers, partially sighted persons may be the group particularly seeking for social relations (Vuletić, Šarlija & Benjak, 2016;Kasiram & Subrayen, 2013).…”
Section: Discussionmentioning
confidence: 99%